Pembenihan Ikan Patin Siam (Pangasius hypophthalamus) Menggunakan Induksi Hormon HCG (Human Chrorionic Gonadotropin) Dan Ovaprim Di Dinas Kelautan Dan Perikanan Subang, Jawa Barat - Wahyu Puji Astiyani; Ega Aditya Prama; Irvan Firmansyah; Jaziroh Rizky Wulandari (Faculty of Science and Technology University Ibrahimy, 2021)
Pangasius sp. is a mainstay commodity in Indonesia. Economically Pangasius sp., is promising to be developed as an export commodity. Hatcheries of Pangasius sp. are carried out at the Marine and Fisheries Service Branch Subang. Data analysis in this research used quantitative descriptive analysis and qualitative descriptive analysis. The results of the research that Pangasius sp. can issue 323.500 eggs per broodstock with the egg weight released by each broodstock was 300 gr. The productivity of Pangasius sp. eggs can reach 5.176.000 eggs with Hatching Rate 99.6 %. The survival rate was 85 %. Analysis of the Pangasius sp. hatchery business after analyzing the R/C ratio resulted in a value of 2.9 where this business could provide a large income in a monthly cycle.